Development of functional gastrointestinal disorder symptoms following laparoscopic cholecystectomy: a prospective cohort study - Chang, Ji Young; Jung, Hye-Kyung; Moon, Chang Mo; Kim, Seong-Eun; Shim, Ki-Nam; Jung, Sung-Ae; Min, Seog Ki (Frontiers in Medicine, 2023)
Background The casual relationship between the role of cholecystectomy and functional gastrointestinal disorders (FGIDs) are a controversial clinical challenge. This study aimed to investigate: (1) the overlap of FGIDs before cholecystectomy and its long-term outcome after surgery in patients with symptomatic cholelithiasis, and (2) the incidence of new-onset FGIDs after cholecystectomy. Methods Patients with symptomatic gallstone disease who underwent elective, laparoscopic cholecystectomy were prospectively enrolled. Healthy populations who underwent medical check-ups were selected as age- and sex-matched controls. Questionnaires regarding sociodemographic characteristics, gastrointestinal symptoms and a somatization symptom checklist (SSC) were completed at baseline and 12 months thereafter. Results The prevalence of all FGID symptoms before cholecystectomy were significantly higher in the group of patients with symptomatic cholecystolithiasis compared to the control group. In cholecystectomy group, the preoperative FGID symptoms improved after surgery, except for chronic diarrhea. Compared to the controls, the new-onset FGIDs, including functional dyspepsia (14.8% vs. 6.9%; p = 0.040), functional diarrhea (6.6% vs. 0.2%; p < 0.001), and chronic abdominal pain (11.9% vs. 4.4%; p = 0.024), were more common at 1 year after cholecystectomy. Somatization was independent predictors of new-onset dyspepsia and abdominal pain, while newly occurring diarrhea was not realted to somatization. Conclusion Overlap of FGIDs was common in patients with symptomatic cholelithiasis before surgery and at follow-up 1 year after cholecystectomy. Furthermore, new-onset FGIDs could be occurred after cholecystectomy. Therefore, a delicate diagnostic approaches and appropriate treatments about co-existent FGIDs should be given in patients with cholelithiasis before and after cholecystectomy.